4 - Prix officiels et Prix d'Equilibre des Denrées alimentaires: le Cas du Maïs et du Mil à Lomé: par Mavor Tetey Agbodan - Mavor Tetey Agbodan, (Africa Development, 1989)
ABSTRACT: Public authorities have always sought to control prices not so much of services as of other products. There are generally two objectives but of a varying nature: protection of economic agents mostly urban consumers in Africa and control of fiscal fraud. While the inten- tions are worthy, the measures taken often seem inappropriate and the means used out of pro- portion in comparison with the outcome. At times the measures trigger a boomerang i.e. price inflation instead of stabilization, negative results and general discontent. A case in point is the ensemble of administrative measures taken by TOGOGRAIN to stabilize prices of staple ce- reals, maize, millet, sorghum, beans and rice. To meet its objectives of developing food pro- ducts through sufficiently remunerative prices to producers, stabilization of the price of consumption and forwaming against deficits, TOGOGRAIN uses moral persuasion, price fixing, banning of exports and detention. The prices paid to producers by TOGOGRAIN are smaller than that offered by wholesalers. A policy of price stabilization should aim at produc- tion and not prices. In Togo, the surface under cultivation is stagnant, the yields are regressive and there has been a significant increase in population. As there is a deficit in maize and millet, products whose consumption rate is very high, these products are imported. Just like at the stock exchange, the traditional African market is very sensitive to the variations of demand and supply as a result of which prices vary many times in the day. Commercial transactions obey neither dictates nor the barrel of the gun. The arbitrary fixing of prices results in withdrawal of produce from the market and the birth of parallel markets both of which further trigger prices. TOGOGRAIN is not viable not because it is subsidized as is European agriculture but because of the discrepancy between the stated objectives and the outcomes.